A reinvenção da ação profissional no programa interdisciplinar de apoio às escolas municipais do Rio de Janeiro: um estudo de caso de duas equipes - Palma, Luciana Braga (2013)
This study aims to analyses the professional action of social workers, teachers and psychologists in an interdisciplinary support to the municipal schools in Rio de Janeiro program. Through two interdisciplinary groups cases studies, in two schools, it was possible to observe the relation between the choice of a certain school and the index of development of the basic education.